Combined association of the triglyceride glucose index and body roundness index with cardiovascular disease in middle-aged and elderly persons with diabetes: a CHARLS-based cohort study - Fan, Xinbiao; Liang, Yongchun; Ge, Jun; Sun, Xitong; Geng, Xiaofei; Zhu, Boyu; Kang, Yuxin; Zhang, Zheng; Zhang, Junping (Frontiers in Nutrition, 2026)
BackgroundInsulin resistance and visceral obesity are key pathologic mechanisms of CVD. However, the combined effect of the triglyceride glucose (TyG) index and body roundness index (BRI) on CVD risk in the diabetic population has not been thoroughly investigated.MethodsThe cohort study used data from four waves of the China Health and Retirement Longitudinal Study (CHARLS) conducted from 2011 to 2018, involving 1,010 participants with diabetes. Participants were categorized according to the median TyG index and/or BRI. Cox proportional risk regression models were used to examine the individual and joint associations of the two metrics with CVD risk. The study further estimated additive and multiplicative interaction effects.ResultsDuring a median follow-up of 7 years, 251 participants developed CVD. The study confirmed a significant joint association between TyG index and BRI and the development of CVD in middle-aged and elderly persons with diabetes. Specifically, after adjusting for confounders, participants with both high TyG index and high BRI had a 123% increased risk of CVD compared with participants with both low TyG index and low BRI, and 85% for high BRI alone. In addition, the study did not find an additive and multiplicative interaction between BRI and TyG index on CVD.ConclusionThis study found that high TyG index and high BRI were significantly associated with increased risk of new-onset CVD in a Chinese middle-aged and elderly diabetic population, and the combined assessment of the TyG index and BRI enhanced the prediction of CVD.